Evidence of Griffith phase in quantum critical region of Dy2Ti1.8Mn0.2O7 - Upadhyay R.; Shukla M.; Sain R.; Tolkiehn M.; Upadhyay C. (My University, 2025)
We herein present the spin freezing dynamics of doped polycrystalline compound Dy2Ti1.8Mn0.2O7 using ac and dc magnetic measurements. A new relaxation peak (T*) appears in ac susceptibility measurement with the fractional inclusion of Mn at the Ti site in Dy2Ti2O7, indicating the presence of a short-range magnetically ordered state in the paramagnetic state. The evidence of the ‘Griffiths phase’-like state has been observed in the quantum critical region of Dy2Ti1.8Mn0.2O7. Arrhenius fit of freezing temperature (T*) with frequency for Dy2Ti1.8Mn0.2O7 shows that the spin relaxation at T* is thermally induced. Low-temperature structural change in lattice parameters and crystal field phonon coupling has been studied using synchrotron X-ray diffraction. Debye-Grüneisen's temperature-dependent lattice-volume analysis shows the ‘crystal field’-phonon coupling emergence at a much higher temperature (70 K) in Dy2Ti1.8Mn0.2O7 in contrast to 30 K in Dy2Ti2O7. These findings make Dy2Ti1.8Mn0.2O7 a suitable system to explore the application of the spin ice phenomenon at a workable temperature. © 2022 Elsevier B.V.